Notulae to the Italian alien vascular flora: 3 - Gabriele Galasso; Gianniantonio Domina; Nicola M.G. Ardenghi; Silvia Assini; Enrico Banfi; Fabrizio Bartolucci; Valentina Bigagli; Gianmaria Bonari; Emanuel Bonivento; Paolo Cauzzi; Francesco S. D’Amico; Marco D’Antraccoli; et al. (Italian Botanist, 2017)
In this contribution, new data concerning the Italian distribution of alien vascular flora are presented. It includes new records, exclusions, confirmations, and status changes for Italy or for Italian administrative regions for taxa in the genera Acer, Amaranthus, Araujia, Aubrieta, Avena, Bidens, Calycanthus, Celtis, Elaeagnus, Eragrostis, Euonymus, Fallopia, Ficus, Hedera, Lantana, Ligustrum, Ludwigia, Morus, Oenothera, Opuntia, Oxalis, Parkinsonia, Paspalum, Paulownia, Platycladus, Pleuropterus, Rumex, Salvia, Senecio, Setaria, Syagrus, Tradescantia, Trifolium and Yucca. Furthermore, a new combination in the genus Vicia is proposed.